Development of a Historical Thinking Skills Assessment Instrument Based on the Evalbee Application for Colonialism and Imperialism Material in High School Students - Agustin, Anik Selviana; Wasino, Wasino; Yuwono, Agus (Lembaga Riset dan Inovasi Almatani, 2025)
Historical thinking skills are a crucial element within the Merdeka Curriculum. These skills can be defined as the scientific procedures or steps involved in learning history. This research aimed to develop an assessment of historical thinking skills for high school students using the Evalbee application. The study employed a Research and Development (R&D) methodology, specifically the ADDIE model. The developed instrument was deemed feasible based on expert validation and empirical trial evidence. The feasibility achievement included an expert validity score of 0.91, falling within the